(3GdJMaI GdLGeYI deaQOGJ GdWH GdfGaYIs - (3GdYGeQj GdMQVj , jMji Hf CHj HcQ Hf eMeO, CHh RcQjG,J (B893 (3g` s ((3eUWai Hf eMeO GdHSfhj s)
(3ChdgG (B:s
(3GdMeO ddg NGdb GdCLSGe heG jYQV dgG ef GdCde hGdVQQ aEf Yde GdWH VQhQj, jTgO dTQag hUMJg Gdfbd hGdYbd s
(3BNQgG (B:s
(3ef BNQ cdGeg dG Edg EdG Gddg ONd GdLfI Gddge GNJe dfG HgG eY GdQhM hGdQjMGf hGdYah hGdQVhGf s
(3Vef eLehY , JQJjHgG (B: (3ef U (B77 - (3U(B161s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B9 - (3U (B168s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B46 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs